Determination of the reduction factor of 110 kV cable line - Mrvić, Jovan; Jasika, Ranko (Proceedings, Electrical engineering institute "Nikola Tesla", 2020)
The paper presents the procedure for determining the reduction factor of 110 kV cable line based on the measurement results. The obtained results were compared with the values obtained by cable line modeling in the ATP/EMTP software tool. The values of the reduction factor are compared, as well as the values of the induced voltage in the cable sheath. The obtained results show a fairly good agreement between the simulation model and measurements. In the formed model, the influence of soil resistivity and conductors arrangement on the values of the reduction factor were analyzed. It has been shown that the impact can be significant.
Keywords: ATP/EMTP, cable, reduction factor, sheath